Peran Lembaga Pemberdayaan Masyarakat Kelurahan (LPMK) Dalam Mendorong Partisipasi Masyarakat (Studi Kasus Lpmk Lamper Kidul, Kecamatan Semarang Selatan, Kota Semarang) - Nadia Augtaria Putri (Journal of Politic and Government Studies, 2026)
Community empowerment is a strategic process to increase the community's independence, participation, and bargaining position in development. One of the empowerment instruments at the village level is the Village Community Empowerment Institution (LPMK) which acts as a government partner in accommodating aspirations, encouraging participation, and planning and supervising development in a participatory manner. However, the implementation of the role and function of LPMK in Lamper Kidul Village, South Semarang District, Semarang City, has not been running optimally due to various institutional and coordination constraints. Therefore, this study aims to analyze the role of LPMK in encouraging community participation to increase empowerment in Lamper Kidul Village. This study uses the institutional role of community empowerment as proposed by Alfitri (2011) with a descriptive qualitative method (Creswell, 2007). The research data was obtained through interview and observation techniques to explore in depth the role of LPMK Lamper Kidul in encouraging community participation. The results of the study show that the role of LPMK Lamper Kidul in encouraging community participation has not run optimally at all stages of empowerment. LPMK tends to function formally as a coordinator and distributor of information, without being balanced with active involvement in aspiration exploration, participatory planning, inclusive implementation, and systematic evaluation. Weak internal capacity, low transparency, limited communication, and lack of socialization have an impact on low public participation and trust. This condition causes community empowerment in Lamper Kidul Village to be more formalistic and has not been able to answer the real needs of residents.